2017
DOI: 10.1186/s12918-017-0394-4
|View full text |Cite
|
Sign up to set email alerts
|

Markov State Models of gene regulatory networks

Abstract: BackgroundGene regulatory networks with dynamics characterized by multiple stable states underlie cell fate-decisions. Quantitative models that can link molecular-level knowledge of gene regulation to a global understanding of network dynamics have the potential to guide cell-reprogramming strategies. Networks are often modeled by the stochastic Chemical Master Equation, but methods for systematic identification of key properties of the global dynamics are currently lacking.ResultsThe method identifies the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 90 publications
5
31
0
Order By: Relevance
“…3B). In agreement with previous studies 52, 53 , the identified metastable states were not recovered from deterministic simulations of the governing ordinary differential equations (Supplementary Information), but could only be identified directly from the stochastic data (Fig. 3A,B).…”
Section: Gene Regulatory Networksupporting
confidence: 91%
See 1 more Smart Citation
“…3B). In agreement with previous studies 52, 53 , the identified metastable states were not recovered from deterministic simulations of the governing ordinary differential equations (Supplementary Information), but could only be identified directly from the stochastic data (Fig. 3A,B).…”
Section: Gene Regulatory Networksupporting
confidence: 91%
“…By contrast, we show here that protein folding pathways and rates can be recovered without explicit knowledge of the time-dependent trajectories, provided the system is sufficiently ergodic and equilibrium distributions are sampled accurately. Furthermore, we show that the dynamics of state-switching or phenotype-switching in gene regulatory networks 51 can be inferred directly from static snapshots of protein abundances in regimes where deterministic modeling only captures a single steady state 52,53 . The agreement of our FIG.…”
Section: Introductionmentioning
confidence: 99%
“…We define two types of model systems. The Mutual Inhibition/Self-Activation (MISA) model encodes a common network motif that is understood to control a variety of cell fate decisions (Graf and Enver, 2009;Huang, 2013) and has been extensively studied by mathematical modeling (Huang et al, 2007;Feng and Wang, 2012;Chu et al, 2017). In contrast, the Two-Gene Flex model flexibly encodes a variety of regulatory interactions, as described below.…”
Section: Discrete Stochastic Models Of Two-gene Regulatory Networkmentioning
confidence: 99%
“…That is, it assumes the propensity of reactions that lead to mRNA numbers exceeding M − 1 is 0. This assumption is justified when M is chosen to be sufficiently large compared to g/k (Chu et al, 2017). We confirmed that the probability of mRNAs exceeding M-1 for our parameter values is negligible (Supplement, Section 2.2) and we further confirmed that increasing M (from 21, the value used in calculations throughout the manuscript, to 36) had negligible impact on quasipotential landscape shape and all subsequent analysis of single cell RNA sequencing (scRNA-seq) data ( Figure S2).…”
Section: Chemical Master Equationmentioning
confidence: 99%
“…By contrast, we show here that protein-folding pathways and rates can be recovered without explicit knowledge of the time-dependent trajectories, provided the system is sufficiently ergodic and equilibrium distributions are sampled accurately. Furthermore, we show that the dynamics of state-switching or phenotype-switching in generegulatory networks 40 can be inferred directly from static snapshots of protein abundances in regimes where deterministic modeling only captures a single steady state 41,42 . The agreement of our inferred results with two separate sets of time-dependent measurements suggests that the inference of complex transition networks via reconstructed energy landscapes can provide a viable and often more efficient alternative to traditional timeseries estimates, particularly as new experimental techniques will offer unprecedented access to high-dimensional ensemble data.…”
mentioning
confidence: 99%